Advanced age, constipation, depression: what are the ways of management? - N. P. Chernus; L. A. Vinogradova; N. V. Kireeva (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2013)
Constipation is one of the key problems of modern therapy for elderly people. The research aim was to study the features of the psychological and microbiological status of the advanced and senile age patients with functional constipation and to see the effect of educational programmes on compliance of the patients with the therapy in the out!patient departments. The investigation showed that depression was more frequent in the patients of group 1 (68.4 % of the cases) with compensated function of the large gut whereas in the 2nd group – 34.6 % (compensated) and in the 3rd group – 41.5 % (subcompensated)cases. The 3rd degree dysbiosis was found in all patoents irrespective of the extern of disorder of the motor!kinetic function in the large gut.